2012
DOI: 10.1242/dev.081554
|View full text |Cite
|
Sign up to set email alerts
|

Giant meiotic spindles in males from Drosophila species with giant sperm tails

Abstract: The spindle is a highly dynamic molecular machine that mediates precise chromosome segregation during cell division. Spindle size can vary dramatically, not only between species but also between different cells of the same organism. However, the reasons for spindle size variability are largely unknown. Here we show that variations in spindle size can be linked to a precise developmental requirement. Drosophila species have dramatically different sperm flagella that range in length from 0.3 mm in D. persimilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…To date, all spindle scaling data is derived from mitotic spindle measurements [14] with the exception of data from male meiosis in Drosophila [23] and studies using unfertilized X. laevis egg cytoplasm, which recapitulates meiotic spindle assembly in vitro using demembranated sperm nuclei [2,7,24]. To examine female meiotic spindle features more broadly we fixed, stained and imaged eggs from ten organisms representing six different phyla (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…To date, all spindle scaling data is derived from mitotic spindle measurements [14] with the exception of data from male meiosis in Drosophila [23] and studies using unfertilized X. laevis egg cytoplasm, which recapitulates meiotic spindle assembly in vitro using demembranated sperm nuclei [2,7,24]. To examine female meiotic spindle features more broadly we fixed, stained and imaged eggs from ten organisms representing six different phyla (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in the other D. melanogaster cell types, metaphase chromosomes occupy the entire equatorial region of the spindle or even protrude from the spindle (Fig. 3; [30]). A recent study provided a likely explanation for the disproportionate MT content of male meiotic spindles.…”
Section: Spindle Formation In Meiotic Cells Of Drosophila Malesmentioning
confidence: 93%
“…Cytological analysis of male meiosis in six different Drosophila species that exhibit dramatic differences in sperm tail length (e.g. 0.3 mm in Drosophila persimilis, 1.8 mm in Drosophila melanogaster, and 58.3 mm in Drosophila bifurca) showed that these species also exhibit striking variations in meiotic spindle size [30]. These variations positively correlate with sperm length, with D. bifurca showing a 30-fold larger spindle than D. persimilis.…”
Section: Spindle Formation In Meiotic Cells Of Drosophila Malesmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in telophase I and II, the meiotic spindle is about 27 and 20 lm, respectively [Lattao and Bonaccorsi, 2012].…”
Section: Component Of Chromosomal Passenger Complexmentioning
confidence: 99%